2023
DOI: 10.1107/s2059798322011901
|View full text |Cite
|
Sign up to set email alerts
|

Errors in structural biology are not the exception

Abstract: During the COVID-19 pandemic, the structural biology community swung into action quickly and efficiently, and many urgent questions were solved by macromolecular structure determination. The Coronavirus Structural Task Force evaluated all structures from SARS-CoV-1 and SARS-CoV-2, but errors in measurement, data processing and modelling are present beyond these structures and throughout the structures deposited in the Protein Data Bank. Identifying them is only the first step; in order to minimize the impact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Larger Mg 2+ numbers result habitually from specific buffer conditions or from an excess of faith in the amount of information contained in experimental data. For RNA and other metal containing biomolecular systems, the latter bias has been documented (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and some tools to identify assignment errors have been developed (24)(25)(26) but none specific to nucleic acids besides the MgRNA attempt (27) that has been critically evaluated (14,15). Thus, it is essential to advance our understanding of the binding stereochemistry of Mg 2+ and K + ions to rRNA to correctly assign these ions to the peaks derived from experimental cryo-EM/X-ray density maps and to get more insights into their biological functions.…”
Section: Introductionmentioning
confidence: 97%
“…Larger Mg 2+ numbers result habitually from specific buffer conditions or from an excess of faith in the amount of information contained in experimental data. For RNA and other metal containing biomolecular systems, the latter bias has been documented (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and some tools to identify assignment errors have been developed (24)(25)(26) but none specific to nucleic acids besides the MgRNA attempt (27) that has been critically evaluated (14,15). Thus, it is essential to advance our understanding of the binding stereochemistry of Mg 2+ and K + ions to rRNA to correctly assign these ions to the peaks derived from experimental cryo-EM/X-ray density maps and to get more insights into their biological functions.…”
Section: Introductionmentioning
confidence: 97%
“…At resolutions better than 3 Å, experts can build atomic models with few errors, whereas at resolutions below 4 Å, avoiding mistakes is challenging. It is therefore not uncommon for atomic models of biological complexes to contain errors ( 7 ), with potentially grievous consequences ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the quality of experimentally resolved structures can vary significantly 17 . Efforts have been made to establish criteria for assessing the quality of such structures, like the Iridium criteria 18 .…”
Section: Introductionmentioning
confidence: 99%